Aliphatic Quaternary Ammonium Functionalized Nanogels for Gene Delivery - Huaiying Zhang; Damla Keskin; Willy H. de Haan-Visser; Guangyue Zu; Patrick van Rijn; Inge S. Zuhorn (MDPI AG, 2021)
Gene therapy is a promising treatment for hereditary diseases, as well as acquired genetic diseases, including cancer. Facing the complicated physiological and pathological environment in vivo, developing efficient non-viral gene vectors is needed for their clinical application. Here, poly(N-isopropylacrylamide) (p(NIPAM)) nanogels are presented with either protonatable tertiary amine groups or permanently charged quaternized ammonium groups to achieve DNA complexation ability. In addition, a quaternary ammonium-functionalized nanogel was further provided with an aliphatic moiety using 1-bromododecane to add a membrane-interacting structure to ultimately facilitate intracellular release of the genetic material. The ability of the tertiary amine-, quaternized ammonium-, and aliphatic quaternized ammonium-functionalized p(NIPAM) nanogels (i.e., NGs, NGs-MI, and NGs-BDD, respectively) to mediate gene transfection was evaluated by fluorescence microscopy and flow cytometry. It is observed that NGs-BDD/pDNA complexes exhibit efficient gene loading, gene protection ability, and intracellular uptake similar to that of NGs-MI/pDNA complexes. However, only the NGs-BDD/pDNA complexes show a notable gene transfer efficiency, which can be ascribed to their ability to mediate DNA escape from endosomes. We conclude that NGs-BDD displays a cationic lipid-like behavior that facilitates endosomal escape by perturbing the endosomal/lysosomal membrane. These findings demonstrate that the presence of aliphatic chains within the nanogel is instrumental in accomplishing gene delivery, which provides a rationale for the further development of nanogel-based gene delivery systems.